2004
DOI: 10.1128/jb.186.20.6837-6844.2004
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptional Regulator AlgR Controls Cyanide Production in Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa is an opportunistic pathogen that causes chronic lung infections in cystic fibrosis (CF) patients. One characteristic of P. aeruginosa CF isolates is the overproduction of the exopolysaccharide alginate, controlled by AlgR. Transcriptional profiling analyses comparing mucoid P. aeruginosa strains to their isogenic algR deletion strains showed that the transcription of cyanide-synthesizing genes (hcnAB) was ϳ3-fold lower in the algR mutants. S1 nuclease protection assays corroborated thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
76
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 57 publications
5
76
2
Order By: Relevance
“…In vitro data suggests that mucoid P. aeruginosa isolates produce more cyanide than nonmucoid laboratory strains [5], but such a relationship was not identified in the present study as all patients were colonised with mucoid strains (data not shown). Whether strains that produce more cyanide have a survival advantage in the CF lung environment or whether the alginate layer in mucoid strains simply increases cyanide output by limiting oxygen diffusion are questions that need to be examined further.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…In vitro data suggests that mucoid P. aeruginosa isolates produce more cyanide than nonmucoid laboratory strains [5], but such a relationship was not identified in the present study as all patients were colonised with mucoid strains (data not shown). Whether strains that produce more cyanide have a survival advantage in the CF lung environment or whether the alginate layer in mucoid strains simply increases cyanide output by limiting oxygen diffusion are questions that need to be examined further.…”
Section: Discussioncontrasting
confidence: 70%
“…In CF airways, P. aeruginosa is thought to grow in anaerobic/reduced oxygen pockets situated within thickened and tenacious mucus plugs that occlude small airways [3,4]. This environment may be suitable for cyanide production by P. aeruginosa [5][6][7]. However, to date, it is not known whether bacteria are residing in strictly anaerobic or microaerobic pockets within the CF lung.…”
mentioning
confidence: 99%
“…It has been described that clinical isolates of P. aeruginosa produced high levels of cyanide (22) as a secondary metabolite (23) and that cyanide can be a relevant determinant for the virulence of P. aeruginosa in wounds from burn patients (24) as well as in lung infections of CF patients (22). Because cyanide has also been described as a relevant element in the infectiondriven killing of C. elegans by P. aeruginosa (25), we have analyzed the effect of this compound in the physiology of the wild-type and the evolved C. elegans strains.…”
Section: Resultsmentioning
confidence: 99%
“…AlgR regulates the hcnABC operon genes (PA2193-PA2195) involved in hydrogen cyanide synthesis in P. aeruginosa (480). In the ampR mutant, these genes are downregulated five-to seven-fold without a corresponding significant differential regulation of algR (< two-fold).…”
Section: Phenotypic Microarray Analysis Of Pao∆amprmentioning
confidence: 99%
“…In addition to regulating the algD operon, AlgR directly activates transcription of algC (PA5322), which encodes a phosphomannomutase/phosphoglucomutase essential for Psl, alginate and rhamnolipid synthesis ( Figure 6.2) (739-742). AlgR also is important for mature biofilm formation, possibly by directly repressing rhl-QS (743), type IV pilus formation by binding to the fimTU-pilVWXY1Y2E promoter (744,745), and hydrogen cyanide (HCN) production by binding to the hcnA (PA2193) promoter (480). Interestingly, in contrast to alginate production, the phosphorylation site is required for regulating cyanide production and twitching motility (744,746).…”
Section: Alginate Productionmentioning
confidence: 99%